PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) PADA BERBAGAI JENIS MULSA - Darmo Asamin; Hasmari Noer; Sayani Sayani (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to determine and explore the growth and yield of tomato plants in various types of mulch carried out in Maku Village, Biromaru District, Sigi Regency, Central Sulawesi Province. This study was designed using a randomized block design (RAK) of one factor grouped based on plant seed height. The treatment that was tried was to share the type of mulch (M), the treatment of the study was as follows: without mulch, black silver plastic mulch, transparent plastic mulch, 10 t / ha wood sawdust and 10 t / ha rice straw. Each treatment was repeated three times so that there were 15 experimental plots. To find out the effect of the treatment being tried, a variance analysis of 0.05 was carried out. Analysis of variance that showed a significant effect, carried out further tests BNJ α = 0.05. The results of the study showed that the use of various types of mulch had a significant effect on the growth and yield of tomato plants. 10 t / ha straw mulch gives better growth rates and yields of tomato plants, respectively; the height of tomato plants aged 3 and 6 MST was 34.37 cm and 70.27 cm, stem diameters of 3 and 6 weeks were 2.31 mm and 2.41 mm, the number of branches aged 3 and 6 MST was 0.60 and 5.80 pieces, yields I, II and III were 0.93 kg / plot, 0.99 kg / plot and 1.79 kg / plot respectively, the total yield per plot was 3.70 kg / plot and Harvest yield per hectare is 6.17 t / ha.